Examining relationships among technology supportive practices, talent management and rapid technology assimilation to achieve innovation and organisational competitiveness - Kyriacou, Panayiota (Τμήμα Διοίκησης Ξενοδοχείων και Τουρισμού, Σχολή Διοίκησης και Οικονομίας,Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
This study tested the validity of a newly developed model linking technology supportive practices to rapid technology assimilation and talent management and evaluated the causal effects on innovation and organisational competitiveness. The analysis was based on data gathered from a radio and television broadcasting house in Cyprus. Structural equation modeling results ascertained that the rapid technology assimilation was predicted by technology supportive practices, frequency of new technology introduction, reliability of technologies, managerial support for new technologies, employee involvement and participation in technological change and technology specific training. The talent management construct, which was composed of the talent attraction and talent retention sub-scales, was also predicted by the aforementioned technology supportive practices. Rapid technology assimilation and talent management were found to positively relate with product and process innovation. Product and process innovation were found to positively relate with organisational competitiveness.
Keywords: Technology supportive practices; Talent management; Rapid technology assimilation; Innovation; Competitive organisation